Menelaah Fenomena Pendidikan Luar Sekolah dalam Ilmu Antropologi: Kajian Kritis Enkulturasi, Kekuasaan, dan Proses Pelestarian Budaya - Rahmat Zulfikar Hamid; Nurbaeti Nurbaeti; Muh Kasim; Alwi Usra Usman (Haumeni Journal of Education, 2025)
The urgency of studying Non-Formal Education arises from the pressures of modernization and digital disruption, which threaten the preservation of local knowledge. Its relevance lies in understanding the role of Non-Formal Education as a last bastion for enculturation and identity formation amid cultural erosion. This article aims to critically examine it from an anthropological perspective, analyzing the dynamics of enculturation, manifestations of power, and its role in cultural preservation. This qualitative research with an interpretive ethnographic approach uses participant observation and in-depth interviews in indigenous communities, with inductive data analysis. The main findings show that enculturation is a negotiated and selective process driven by youth. However, the presence of asymmetrical power relations, including senior hegemony and gender difference marginalization, results in structural inequalities. Overall, this research was conducted to contribute to Critical Educational Anthropology by presenting a diagnostic model that collaborates power and agency into a framework referred to as enculturation. This conclusion shows that the success of cultural preservation depends on the transformation of out-of-school education into a system that is more inclusive and dialogical for everyone. It is highly recommended that further studies use a mixed-methods approach to measure findings on this phenomenon.